2001
DOI: 10.1063/1.1355284
|View full text |Cite
|
Sign up to set email alerts
|

Local structure analysis of an optically active center in Er-doped ZnO thin film

Abstract: The local structure of an optically active center in erbium-doped zinc oxide (ZnO:Er) thin film produced by a laser ablation technique and its optical activation process are investigated by Er LIII-edge x-ray absorption fine structure analysis using a synchrotron radiation as an x-ray source. In as-ablated ZnO:Er thin film, Er has an approximately five-fold coordination of O surrounded by eight other O atoms as second-nearest neighbors. The high-order coordination of O decreases the Er-related photoluminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 39 publications
3
76
1
2
Order By: Relevance
“…Provided that PL emission was observed at 980 nm (see inset of No emission was observed from the untreated sample which is in good accordance with the PL results, and may be due to the fact that the surrounding of RE is not adequate to realize up-conversion, and consequently a post-deposition annealing process is necessary. In the case of the annealed samples, the emission intensity of the air and vacuum treatments is in agreement with the one observed in conventional PL spectra: the presence of oxygen enhances RE-related emission/absorption, probably by propitiating the generation of ErO 6 regions [6]. The laser annealed samples show, a very poor up-conversion emission for LAS1 and LAS2, whereas an intense emission is displayed by LAS3, owing to the higher laser power employed.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Provided that PL emission was observed at 980 nm (see inset of No emission was observed from the untreated sample which is in good accordance with the PL results, and may be due to the fact that the surrounding of RE is not adequate to realize up-conversion, and consequently a post-deposition annealing process is necessary. In the case of the annealed samples, the emission intensity of the air and vacuum treatments is in agreement with the one observed in conventional PL spectra: the presence of oxygen enhances RE-related emission/absorption, probably by propitiating the generation of ErO 6 regions [6]. The laser annealed samples show, a very poor up-conversion emission for LAS1 and LAS2, whereas an intense emission is displayed by LAS3, owing to the higher laser power employed.…”
Section: Resultssupporting
confidence: 71%
“…The substitutional doping of Er ions in to the ZnO matrix forming a planar ErO 4 conformation results in a non-optically active state, whereas Er ions fully surrounded by oxygen atoms in a pseudo-octahedron structure with a C 4v symmetry (ErO 6 clusters) are optically active centers that allow the 4f-4f transitions to occur [6]. A thermal annealing is necessary to optically activate the Er ions by changing the Er local structure into the form of ErO 6 clusters, either inside the ZnO matrix or at their grain boundaries [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it was experimentally observed that the rare earth luminescence efficiency at room temperature increases with the band gap of the semiconductor [2], wide band gap materials such as GaN are especially promising for possible applications. Rare earth luminescence from Nd, Sm, Eu, Tb, Dy, Ho, Er and Tm has also been reported in the hexagonal II-VI semiconductor ZnO [3][4][5][6][7][8][9][10][11][12]. Interest in zinc oxide has recently increased due to the fact that its structural and semiconducting properties are similar to hexagonal GaN, but that, in comparison to GaN, highquality single crystals of ZnO are easier to grow [13].…”
Section: Cern-ep Ch-1211 Geneva 23 Switzerlandmentioning
confidence: 99%
“…Several methods for producing RE-doped ZnO have been described in the literature, including sintering [3][4][5], wet-chemical synthesis [6,11], laser ablation [7][8][9][10] and co-deposition following evaporation [12]. However, all these methods result in polycrystalline samples, and there exists evidence that the rare earths accumulate at the grain boundaries of polycrystalline ZnO [4].…”
Section: Cern-ep Ch-1211 Geneva 23 Switzerlandmentioning
confidence: 99%